Radiokarbon Bagi Penentuan Umur Candi Bojongmenje di Rancaekek, Jawa Barat - Darwin Alijasa Siregar (Berkala Arkeologi Sangkhakala, 2011)
AbstractThe finding of the temple in Bojongmenje, cangkuang, bandung is a historic event for west java community. Bojongmenje temple site on cemetery land located between the factories, houses and plantation. The visible condition of the archaelogical objects consists of a stone structure which is in west side of the temple building. The discovery of the remains of the temple in Rancaekek must be addressed as a chalenges phenomenon. In west java that there only has a few heritage which is seriously handled. An archaelogical excavation has not been implemented systematic and planned so that the conclusion cannot be made scientifically and rationally. In addition to archaelogicy, to reveal the history it is necessary using other sciences such as palaentology, anthropology, geocronology. One method used to determined the geological and archaelogical events, especially those the occur on period of geological quarter is radiocarbon method.